An Updated Review On Analytical Methods For Estimation Of Azelnidipine And Telmisartan - Eswarudu, M. M.; Roja, P.; Sankar, P. Ravi; Babu, P. Srinivasa (Asian Journal of Pharmaceutical Research and Development, 2022)
High blood pressure, also called hypertension, is a common condition that is characterized by having a higher amount of pressure in blood vessels than normal. Hypertension (HT) is a very common disorder, particularly past middle age. It is not a disease in itself, but is an important risk factor for cardiovascular mortality and morbidity. For improvement activity of hypertension, Azelnidipine and Telmisartan newer combination in market, which is effective in Hypertension. This combination was developed to improve medication for Stage II Hypertension. Azelnidipine is Ca2+ channel blocker and chemically 3-[1-(Benzyldrylazetidin-3-yl] 5-isopropyl- 2- amino 6 methyl-4-(3-nitrophenyl)-1,4- dihydropyridine-3, 5dicarboxylate.Telmisartan is AT1-receptor blocker and Chemically2-{4-[[4-methyl-6-(1-methylbenzimidazol-2yl)-2–propylbenzimidazol-1yl] methyl] biphenyl)-benzoic acid. It provides information about different analytical method development like UV spectrophotometry, HPTLC, HPLC, and LC-MS methods reported for Azelnidipine and Telmisartan for individual and other drug combination. All reported methods found to be simple, accurate, economic, precise and reproducible in nature. This Review focuses on recent development in analytical method development for Azelnidipine and Telmisartan, and there were two methods reported for this combination as per our knowledge.